Pengaruh Kesadaran Kesehatan Dan Produk Makanan Terhadap Minat Beli Restoran Vegetarian Dengan Variabel Moderasi Religiusitas Di Indonesia - Himawan dan Hetty Karunia Tunjungsari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine the characteristics of vegetarian restaurant consumers and to determine the effect of health consciousness and food product on purchase intention at vegetarian restaurant partially in Indonesia. This Study also determine the effect of health consciousness on the relationship with religiosity and the effect of food product on the relationship with religiosity with an purchase intention at vegetarian restaurant in Indonesia.This research uses descriptive quantitative methods. The method of data collection is done using primary data and secondary data. Primary data is obtained from the distribution of questionnaires while secondary data is obtained from other sources. Furthermore, the population in this study were vegetarian restaurant consumers in 5 major cities of Indonesia namely Jakarta, Bandung, Semarang, Surabaya, Medan. This study uses non-probability sampling techniques by taking purposive sampling. The number of samples in this study were 382 respondents. The method of data analysis in this study used multiple regression analysis with the SmartPLS version 3.0 program.The results of this study indicate that health consciousness and food product have a significant influence on purchase intention at vegetarian restaurant partially. Health consciousness and food products have a significant influence on purchase intention which is moderated by religiosity in vegetarian restaurant customers. Furthermore Health consciousness and product to purchase intention will be further strengthened if moderated by religiosity.